2019
DOI: 10.3390/ijerph16132406
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Intelligence and Work–Family Conflict: A Moderated Mediation Model Based on Conservation of Resources Theory

Abstract: This study aims to explore the influence mechanism of cultural intelligence on work–family conflict for Chinese expatriates in cross-cultural non-profit organizations. Drawing on conservation of resources theory, this longitudinal study (six-month time lag) is the first to examine cultural intelligence as an antecedent of work–family conflict. The study also examines the mediating role of work engagement and the moderating role of leader–member exchange (LMX) in the cultural intelligence and work–family confli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 105 publications
(171 reference statements)
1
23
0
Order By: Relevance
“…Despite this, little research has been found that explored the potential correlations between multiple organizational behaviors and work engagement among the physician [ 21 , 22 ]. On the other hand, with the increase of double-income families, work–family conflict, defined as a form of inter-role conflict in which the role pressures from the work and family domains are mutually incompatible in some respect, has become a prominent societal concern, attracting growing attention from researchers and policy makers [ 23 ]. Although some studies have focused on the impact of organizational behavior on employees’ work-family conflict, their participants are mainly enterprise employees, engineering and technical personnel and teachers [ 24 ], less with physicians.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, little research has been found that explored the potential correlations between multiple organizational behaviors and work engagement among the physician [ 21 , 22 ]. On the other hand, with the increase of double-income families, work–family conflict, defined as a form of inter-role conflict in which the role pressures from the work and family domains are mutually incompatible in some respect, has become a prominent societal concern, attracting growing attention from researchers and policy makers [ 23 ]. Although some studies have focused on the impact of organizational behavior on employees’ work-family conflict, their participants are mainly enterprise employees, engineering and technical personnel and teachers [ 24 ], less with physicians.…”
Section: Introductionmentioning
confidence: 99%
“…But it is worth noting that excessive emotional labor will have negative impacts on nurses and nursing organizations if it is not recovered in time, such as threatening nurses’ physical and mental health, increasing nurses’ turnover intention and degree of burnout [ 47 ]. Based on the job demands-resources (JD-R) model [ 48 ] and the conservation of resources (COR) theory [ 49 ], the increase of work resources (such as perceived organizational support) can effectively buffer the negative impact of work demand (such as physical demands and emotional labor). As an important job resource, perceived organizational support can provide material support and spiritual support to nurses, which can promote nurses’ emotional labor, help avoid the negative effects of emotional labor, and improve nurses’ professional values.…”
Section: Discussionmentioning
confidence: 99%
“…The data was measured in two waves with six-month intervals. This mainly served to minimize common method variance concerns, and a six-month lag was found to be appropriate in cross-cultural research (He et al, 2019 ; Şahin et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%